Plexin-B1/RhoGEF–mediated RhoA activation involves the receptor tyrosine kinase ErbB-2 - Swiercz, Jakub M. (The Rockefeller University Press, 2004)
Plexins are widely expressed transmembrane proteins that mediate the effects of semaphorins. The molecular mechanisms of plexin-mediated signal transduction are still rather unclear. Plexin-B1 has recently been shown to mediate activation of RhoA through a stable interaction with the Rho guanine nucleotide exchange factors PDZ-RhoGEF and LARG. However, it is unclear how the activity of plexin-B1 and its downstream effectors is regulated by its ligand Sema4D. Here, we show that plexin-B family members stably associate with the receptor tyrosine kinase ErbB-2. Binding of Sema4D to plexin-B1 stimulates the intrinsic tyrosine kinase activity of ErbB-2, resulting in the phosphorylation of both plexin-B1 and ErbB-2. A dominant-negative form of ErbB-2 blocks Sema4D-induced RhoA activation as well as axonal growth cone collapse in primary hippocampal neurons. Our data indicate that ErbB-2 is an important component of the plexin-B receptor system and that ErbB-2–mediated phosphorylation of plexin-B1 is critically involved in Sema4D-induced RhoA activation, which underlies cellular phenomena downstream of plexin-B1, including axonal growth cone collapse.